Clinical characteristics and oncological outcomes of surgically treated early-onset gastric adenocarcinoma - a retrospective cohort study - Rompen, Ingmar F.; Nienhüser, Henrik; Crnovrsanin, Nerma; Musa, Julian; Haag, Georg Martin; Longerich, Thomas; Fiedler, Timon; Müller, Beat P.; Peters, Leila; Billeter, Adrian (Journal of cancer, 2023)
Introduction: The incidence of early-onset gastric adenocarcinoma (patients <50 years, EOGA) is rising. Tumors in younger patients are associated with prognostically unfavorable features. The impact of EOGA on patient survival, however, remains unclear. The aim of this study is to evaluate early-onset age as a prognostic factor compared to late-onset gastric adenocarcinoma (LOGA, >50years) in a surgical cohort and assesstreatment options. Methods: We analyzed 738 patients (129 early-onset/609 late-onset) operated in curative intent from 2002 to 2021. Data was extracted from a prospectively managed database of an academic tertiary referral hospital. Differences in perioperative as well as oncological outcomes were calculated by chi-square test. Cox regression analysis was performed to assess disease-free survival (DFS) and overall survival (OS). Results: EOGA patients were more often treated with neoadjuvant therapy (62.8% vs. 43.7%, p<0.001) and extended surgical resections e.g. through additional resections (36.4% vs. 26.8%, p=0.027). EOGA was more often metastasized into regional lymph nodes (pN+ 67.4% vs. 55.3%, p=0.012) and to distant sites (pM+: 23.3% vs. 12.0%, p=0.001) and was more often poorly differentiated (G3/G4: 91.1% vs. 67.2%, p<0.001). There were no significant differences in overall complication rates (31.0% vs. 36.6%, p=0.227). Survival analysis showed shorter DFS (median DFS 25.6 months vs. not reached, p=0.006) but similar OS (median OS: 50.5 months vs. not reached, p=0.920) in EOGA compared to LOGA. Conclusions: This analysis confirmed that EOGA is associated with more aggressive tumor characteristics. Early-Onset was not a prognostic factor in the multivariate analysis. EOGA patients may be more capable to undergo intensive multimodal therapy including perioperative chemotherapy and extended surgery.
Veröffentlicht: 21.5.2023
Gesehen am 28.09.2023